Development of Financial Reporting Standards in India - Gurminder Kaur Arora (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
The onset of globalization and increasing interdependence among the world nations through flows of goods, services, human resources, capital, information and culture across borders, has called for radical changes in international accounting and reporting, accepting the entire world as one economy. The IFRS convergence gained momentum all over the world and India was no exception. As the world was going global on a massive scale, the need for convergence seemed to be crucial. The ICAI is making all efforts to ensure that standards are implemented in the same spirit in which they have been formulated. The Ind AS implementation group has been making relentless efforts to make this transition smooth and effective through its various endeavors.